Induction of Broad-Spectrum Protective Immunity against Disparate Cryptococcus Serotypes - Van Dyke, Marley C. Caballero; Chaturvedi, Ashok K.; Hardison, Sarah E.; Leopold Wager, Chrissy M.; Castro-Lopez, Natalia; Hole, Camaron R.; Wozniak, Karen L.; Wormley, Floyd L. (Frontiers in Immunology, 2017)
Cryptococcosis is a fungal disease caused by multiple Cryptococcus serotypes; particularly C. neoformans (serotypes A and D) and C. gattii (serotypes B and C). To date, there is no clinically available vaccine to prevent cryptococcosis. Mice given an experimental pulmonary vaccination with a C. neoformans serotype A strain engineered to produce IFN-γ, denoted H99γ, are protected against a subsequent otherwise lethal experimental infection with C. neoformans serotype A. Thus, we determined the efficacy of immunization with C. neoformans strain H99γ to elicit broad-spectrum protection in BALB/c mice against multiple disparate Cryptococcus serotypes. We observed significantly increased survival rates and significantly decreased pulmonary fungal burden in H99γ immunized mice challenged with Cryptococcus serotypes A, B, or D compared to heat-killed H99γ (HKH99γ) immunized mice. Results indicated that prolonged protection against Cryptococcus serotypes B or D in H99γ immunized mice was CD4+ T cell dependent and associated with the induction of a predominantly Th1-type cytokine responses. Interestingly, immunization with H99γ did not elicit greater protection against challenge with the Cryptococcus serotype C tested either due to low overall virulence of this strain or enhanced capacity of this strain to evade host immunity. Altogether, these studies provide “proof-of-concept” for the development of a cryptococcal vaccine that provides cross-protection against multiple disparate serotypes of Cryptococcus.